2011
DOI: 10.3109/0886022x.2011.589946
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Medicine Referral in Patients Undergoing Continuous Renal Replacement Therapy for Acute Kidney Injury

Abstract: PMC was safe, but referrals were delayed and ineffective in optimizing the utilization of intensive care in patients receiving CRRT. A proactive, "triggered" referral process will likely be necessary to improve timeliness of PMC and reduce duration of non-beneficial life-sustaining therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…98 The high mortality of AKI in the setting of critical illness and the complex and emotionally laden aspects of the decisions associated with initiating or discontinuing renal support suggest that early involvement of palliative care services may be of benefit. 99 Time-limited trials of RRT may be a useful strategy in circumstances in which there is uncertainty of prognosis or when the patient or family/surrogate decision-maker are not prepared to make a definite decision regarding initiating or discontinuing RRT and other life-sustaining care. 100…”
Section: Ethical Issues In Initiating and Discontinuing Rrtmentioning
confidence: 99%
“…98 The high mortality of AKI in the setting of critical illness and the complex and emotionally laden aspects of the decisions associated with initiating or discontinuing renal support suggest that early involvement of palliative care services may be of benefit. 99 Time-limited trials of RRT may be a useful strategy in circumstances in which there is uncertainty of prognosis or when the patient or family/surrogate decision-maker are not prepared to make a definite decision regarding initiating or discontinuing RRT and other life-sustaining care. 100…”
Section: Ethical Issues In Initiating and Discontinuing Rrtmentioning
confidence: 99%
“…One single-center retrospective study showed a trend in delayed referral to PC for patients undergoing CRRT (41). In this cohort, a PC consult was called a median of 9 days after initiation of CRRT and longer (10 versus 4 days) in those who died (41). These results suggest that a more protracted hospital course and slower clinical decline rather than severity of renal injury trigger PC consults.…”
Section: The Role Of Pc In a Critically Ill Patient Undergoing A Tlt mentioning
confidence: 76%
“…Prognosis and decision making should consider other lifesustaining interventions as well as RRT. The complex nature of this decision in addition to the high mortality rate of AKI suggest that early involvement of PC services can benefit all of those involved (41). The evidence for TLTs is limited, and expert recommendations are few (7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations